2016
DOI: 10.1111/ane.12660
|View full text |Cite
|
Sign up to set email alerts
|

Upper motor neuron evaluation in multiple sclerosis patients treated with Sativex®

Abstract: We confirm the presence of CST impairment in MS patients with spasticity. We did not identify structural/electrophysiological correlates that could explain Sativex clinical effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Thus, variables derived using TMS could help to: (1) provide a better understanding of neuropathophysiological events involved in the onset and sequelae of MS [32], (2) predict disease severity and progression for prognostication purposes, and (3) investigate whether rehabilitation therapies [50] and pharmacological treatments [5] are truly acting on the central nervous system to enhance neuroplasticity and recovery [27]. Although recent work has recognized the potential role of TMS in providing biomarkers of central nervous system functioning in MS, conclusions were based on small studies that demonstrated a high risk of bias [27].…”
Section: Transcallosal Inhibition and The Ipsilateral Silent Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, variables derived using TMS could help to: (1) provide a better understanding of neuropathophysiological events involved in the onset and sequelae of MS [32], (2) predict disease severity and progression for prognostication purposes, and (3) investigate whether rehabilitation therapies [50] and pharmacological treatments [5] are truly acting on the central nervous system to enhance neuroplasticity and recovery [27]. Although recent work has recognized the potential role of TMS in providing biomarkers of central nervous system functioning in MS, conclusions were based on small studies that demonstrated a high risk of bias [27].…”
Section: Transcallosal Inhibition and The Ipsilateral Silent Periodmentioning
confidence: 99%
“…Certain biomarkers provide information on neurophysiological processes related to neurologic disease, which allows researchers to predict potential for disease recovery and understand mechanisms of prospective treatments. This is critical information needed to determine how neurorehabilitation may alter neuroplasticity in heterogeneous disorders of the central nervous system such as stroke and multiple sclerosis (MS) [2][3][4][5]. Some biomarkers can be collected and assayed from biological fluid such blood [6,7] or cerebrospinal fluid [7], while others could involve sophisticated imaging techniques such as positron emission tomography or magnetic resonance imaging (MRI) [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It also has a metaplastic effect on the motor cortex but upper motor neurons are spared. This is the main reason behind its analgesic property, improving sensory responses and evoked potentials [156][157][158][159]. However, in an Italian population of patients with MS, around 40% of patients were resistant to the anti-spastic action of the drug [160].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is one of the most common motor neuron diseases in adults, which is more common than middle age [1], [2]. It selectively involves upper and lower motor neurons.…”
Section: Introductionmentioning
confidence: 99%